Scientific-Methodological Conception of the Strategy of Doctoral Training at the university of Medical Sciences Cienfuegos - Norma Mur Villar; Anays Núñez Herrera; Miriam Iglesias León; Alejandro Antuán Díaz Díaz; Mario Ávila Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Aimed at achieving a change in the health professionals continuous development, regarding the obtaining of a Doctor Degree, and committed with this demand, the University of Medical Sciences has designed a Strategy of Doctoral Training in agreement with the certified institutions. Its scientific and methodological conception is defined as the system of ideas about the process of doctoral training which sets the stages and actions characterized by the principles of systemic, contextual character and their systematization and integration . As the main results it is expected to contribute promoting the work which leads to obtaining scientific degree, increase the protagonist action of the teaching and /or assisting department in following the process of doctoral training, to promote networks of collaboration for doctoral and post-doctoral development, to develop management of on innovation and incorporating to the strategy the scientific groups of students linked to doctoral projects and topics developed at the institution.